The law and economics of patent damages, antitrust, and legal process - Langenfeld, James; Fagan, Frank; Clark, Samuel (Emerald Publishing Limited, 2021)
Law and economics research has had an enormous impact on the laws of contracts, torts, property, crimes, corporations, and antitrust, as well as public regulation and fundamental rights. The Law and Economics of Patent Damages, Antitrust, and Legal Process examines several areas of important research by a variety of international scholars. It contains technical papers on the appropriate way to estimate damages in patent disputes, as well as methods for evaluating relevant markets and vertically integrated firms when determining the competitive effects of mergers and other actions. There are also papers on the implication of different legal processes, regulations, and liability rules on consumer welfare, which range from the impact of delays in legal decisions in labour cases in France to issues of criminal liability related to the use of artificial intelligence. This volume of Research in Law and Economics is a must-read for researchers and professionals of patent damages, antitrust, labour, and legal process.
Includes index.
Keywords: Patent suits.; Lost earnings damages.; Patent laws and legislation.; Business & Economics -- Business Law.; Economic theory & philosophy.; elektronické knihy; electronic books